2016
DOI: 10.1371/journal.pone.0167194
|View full text |Cite
|
Sign up to set email alerts
|

ERP Response Unveils Effect of Second Language Manipulation on First Language Processing

Abstract: Lexical access in bilinguals has been considered either selective or non-selective and evidence exists in favor of both hypotheses. We conducted a linguistic experiment to assess whether a bilingual’s language mode influences the processing of first language information. We recorded event related potentials during a semantic priming paradigm with a covert manipulation of the second language (L2) using two types of stimulus presentations (short and long). We observed a significant facilitation of word pairs rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 58 publications
(71 reference statements)
0
16
0
Order By: Relevance
“…One reason why this issue remains unresolved is methodological. Experimental evidence derived from direct neural measures is minimal and often limited to single linguistic properties [72][73][74][75][76] , thus offering only a partial view of this complex brain mechanism. The present study establishes a methodological framework to provide a more comprehensive examination of the language processing system in naturalistic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…One reason why this issue remains unresolved is methodological. Experimental evidence derived from direct neural measures is minimal and often limited to single linguistic properties [72][73][74][75][76] , thus offering only a partial view of this complex brain mechanism. The present study establishes a methodological framework to provide a more comprehensive examination of the language processing system in naturalistic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the probable AD patients showed a "bilingual advantage" in the expression of Alzheimer's clinical syndrome. Bilingualism could increase cognitive reserve through the constant management of two simultaneously active and competing languages [13,40,[45][46][47][48][49][50][51][52][53][54][55][56][57]. Better reserve, with better compensation or masking of worsening cognition, could explain the worse dementia severity as per MMSE scores on presentation for bilinguals.…”
Section: Discussionmentioning
confidence: 99%
“… Paulmann et al (2006) presented the same prime and target words outside the sentence context and observed the mentioned facilitation effect on the N400 across the experiment, concluding that if the context is not constraining enough, it is not possible to inhibit an individual’s L1. Unlike the previous studies, in Khachatryan et al (2016) the experimental stimuli (word-pairs with homograph primes) were presented in subjects’ L1 only and, the effect of L2 interference in L1 processing was shown to depend on the experimental conditions. Here, it was shown that, when subjects suspected that their L2 knowledge is important for the experiment, the processing of words related to the L2 meaning of the homograph was facilitated.…”
Section: Introductionmentioning
confidence: 85%
“…Therefore, the evaluation of the experimental paradigm involving them will give us a clearer overview on L2 interference in L1 processing in bilingual patients with aphasia. The studies on healthy bilinguals showed that depending on experimental conditions, such as task ( Dijkstra et al, 1998 ), type of stimulus ( van Heuven et al, 1998 ) and even one’s awareness about the importance of L2 in the experiment ( Khachatryan et al, 2016 ), the processing of inter-lingual homograph can be facilitated, inhibited or processed similar to any other word of the studied lexicon.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation